Laparoscopic Cholecystectomy is Safe in Emergency General Surgery Patients with Cirrhosis. Issue 10 (October 2019) - Okamuro, Kyle; Cui, Brian; Moazzez, Ashkan; Park, Hayoung; Putnam, Brant; Virgilio, Chris De; Neville, Angela; Singer, George; Deane, Molly; Chong, Vincent; Kim, Dennis Y.
Cirrhosis is associated with adverse outcomes after emergency general surgery (EGS). The objective of this study was to determine the safety of laparoscopic cholecystectomy (LC) in EGS patients with cirrhosis. We performed a two-year retrospective cohort analysis of adult patients who underwent LC for symptomatic gallstones. The primary outcome was the incidence of intraoperative complications. Of 796 patients, 59 (7.4%) were cirrhotic, with a median model for end-stage liver disease (MELD) score of 15 (IQR, 7). On unadjusted analysis, patients with cirrhosis were older, more likely to be male (both P < 0.01), diabetic ( P < 0.001), had a higher incidence of preadmission antithrombotic therapy use ( P < 0.02), and experienced a longer time to surgery (3.2 vs 1.8 days, P < 0.001). Coarsened exact matching revealed no difference in intra- or postoperative complications between groups ( P = 0.67). Operative duration was longer in patients with cirrhosis (162 vs 114 minutes, P = 0.001), who also had a nonsignificant increase in the rate of conversion to an open cholecystectomy (14% vs 4%, P = 0.07). The results of this study indicate that LC may be safely performed in EGS patients with cirrhosis.